2019
DOI: 10.1016/j.ijpddr.2019.08.002
|View full text |Cite
|
Sign up to set email alerts
|

The combination therapy of meglumine antimoniate and oxiranes (epoxy-α-lapachone and epoxymethyl-lawsone) enhance the leishmanicidal effect in mice infected by Leishmania (Leishmania) amazonensis

Abstract: Current treatment of cutaneous leishmaniasis includes pentavalent antimonials as first-line drugs, but this therapy has shown severe adverse effects. An alternative to minimize this issue is based on combination therapy scheme with other drugs. In this study we analyzed the potential of the association of meglumine antimoniate (MA) with the oxiranes epoxy-α-lapachone (LAP) or epoxymethyl-lawsone (LAW). Results demonstrated that association between these drugs enhanced leishmanicidal activity on Lei… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
20
0

Year Published

2020
2020
2022
2022

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 21 publications
(20 citation statements)
references
References 55 publications
0
20
0
Order By: Relevance
“…Thus, the rational development of new chemotherapy based on functional interconnectivity between energy metabolism, electron transport chain, and lipid biosynthesis enzymes are an approach with high selectivity and effectiveness in the treatment of leishmaniases. In fact, Lap and Law compounds can act as a multi-target drugs, not only based on the results of this study, but also the set of mechanisms previously described in the literature [19,21,22]. These are potential and attractive compounds for new drugs, acting on more than one enzymatic target of Leishmania spp.…”
Section: Resultsmentioning
confidence: 53%
See 1 more Smart Citation
“…Thus, the rational development of new chemotherapy based on functional interconnectivity between energy metabolism, electron transport chain, and lipid biosynthesis enzymes are an approach with high selectivity and effectiveness in the treatment of leishmaniases. In fact, Lap and Law compounds can act as a multi-target drugs, not only based on the results of this study, but also the set of mechanisms previously described in the literature [19,21,22]. These are potential and attractive compounds for new drugs, acting on more than one enzymatic target of Leishmania spp.…”
Section: Resultsmentioning
confidence: 53%
“…Naphthoquinones, a particular group of quinones, and their derivatives have a wide spectrum of biological activities and represent a group of interesting compounds for chemotherapy. Among these compounds, we highlighted two oxiranes, epoxy-α-lapachone (Lap: 2,2-dimethyl-3,4-dihydrospiro[benzo[g]chromene-10,20oxiran]-5(2H)-one)) and epoxymethyl-lawsone (Law: 2-methyl-4H-spiro-[naphthalene-1,20-oxiran]-4-one), (Figure 1), which have been shown to have potential to be used in the treatment of leishmaniases [18][19][20][21][22].…”
Section: Introductionmentioning
confidence: 99%
“…The combination of meglumine antimoniate with 8.8 mg/kg/day of spironolactone was more effective than treatment with meglumine antimoniate alone. Some studies have shown that the use of meglumine antimoniate associated with other drugs is effective; for example, combinations with lapachone derivatives, azoles, amiodarone, and aminosidine sulfate have shown a greater effectiveness when compared to the use of meglumine antimoniate alone (Oliva et al, 1998;Anversa et al, 2017;Gonçalves-Oliveira et al, 2019). Giannitrapani et al (2009) described the case of a patient with visceral leishmaniasis who was previously diagnosed with cirrhosis.…”
Section: Discussionmentioning
confidence: 99%
“…Many studies emphasise that combination therapy not only results in increased efficacy in treating CL but also reduces the dose of each drug, adverse side effects, duration, and the risk of emergence of drug resistance [109,[125][126][127]. Hence, the combination therapy is of great importance.…”
Section: Combination Of Treatment Methodsmentioning
confidence: 99%
“…Cutaneous leishmaniasis due to L. braziliensis in Bolivia gave a CR of 92% (46 patients out of 50) once treated by miltefosine and intralesional pentamidine combination therapy. There was an increment of CL-related antileishmanial activity of MA after combination with oxiranes [ 126 ]. However, a recent in vitro study elucidated the possibility of emerging resistance in L. donovani against drug combinations like miltefosine plus PM and Sb(III) plus PM [ 136 ], For diffuse CL, 60 days’ treatment regimen of pentavalent 20 mg antimonial/kg plus 15 mg PM/kg was superior for L. aethiopica CL, over their respective monotherapies [ 42 ].…”
Section: Combination Of Treatment Methodsmentioning
confidence: 99%